Karakter ideal seorang ayah dalam Surat Yusuf - Muhammad Suaidi Yusuf; Humam Fikri Muzafar (Jurnal Pendidikan Luar Sekolah, 2020)
The research studied the family education message contained in the surah of Yusuf consisting of the characters possessed by the father. Recognizing the ideal characteristics of fathers in the Quran can make a valuable contribution in the study and practice of family education. The study was conducted by the method of tafsir maudhu'i by examining the interpretation of parts of the verse in the letter of Yusuf which contains a dialogue between father and son, namely between the Prophet Yaqub and his sons, Yusuf. The study found that there were 9 characters of a father in the Prophet Yaqub, namely 1) love and affection for, 2) good listeners, 3) patience with children, 4) avoiding and maintaining family conflicts, 5) trusting for the difficulties experienced by the family, 6) Not Desperate, 7) complaining about difficulties and difficulties only to God, 8) forgiving of family and 9) protecting family AbstrakPenelitian mengkaji pesan pendidikan keluarga yang terkandung dalam surat Yusuf berupa karakter-karakter yang dimiliki seorang ayah. Mengenali karakter-karakter ideal seorang ayah dalam al Quran bisa memberikan sumbangan teoritis berharga dalam kajian dan praktek pendidikan keluarga. Penelitian dilakukan dengan metode tafsir maudhu’i dengan mengkaji tafsir bagian-bagian ayat dalam surat Yusuf yang berisi dialog antara ayah dan anak, yakni antara Nabi Yaqub dan putra-putranya. Penelitian menemukan ada 9 karakter seorang ayah dalam diri Nabi Yaqub yaitu 1) cinta dan sayang terhadap, 2) pendengar yang baik, 3) sabar terhadap anak, 4) menghindari dan menjaga konflik keluarga, 5) tawakal atas kesulitan yang dialami keluarga, 6) Tidak Putus asa , 7) mengadukan kesulitan dan kesusahan hanya kepada Allah, 8) pemaaf terhadap keluarga dan 9) pelindung bagi keluarga.